Catering menu management / Nancy Loman Scanlon. - Scanlon, Nancy Loman. (Wiley, 1992)
"Profitable menu management is the engine driving your entire foodservice operation. Without a well-thought-out, well-structured menu, your catering business is at a standstill. Catering Menu Management is a detailed guide to creating and managing a menu efficiently and professionally. It shows you how effective menu management can help you to identify your target market, give your operation a distinctive and attractive style, and ensure profitability. It is the only book devoted exclusively to this essential topic." "Catering Menu Management explains the many considerations--both food and non-food--that go into catering menu development, shows you the proper way to price, gives you guidance on the ideal food/beverage mix, details the ways in which menu management can ease day-to-day operations, and much more. Catering Menu Management gives you a complete overview of:" "The background and history of catering and banqueting: early banqueting styles, nineteenth century changes, and Presidential banqueting, from Martha Washington to Jacqueline Kennedy;" "Your options in catering operations: advantages and disadvantages of various styles of catering operation, from full service restaurants to independent caterers to delicatessens;" "Marketing: how to identify your target market, develop a customer profile, and investigate your competition;" "Pricing and controls: how to determine profitability, select profitable pricing methods, and maintain successful pricing;" "Beverage management: beverage pricing methods, arriving at the ideal food/beverage mix, and handling customer relations."